Malta : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This Selected Issues paper uses a multivariate filter approach to reassess potential output for Malta, given national account data revisions and the ongoing labor market changes. The analysis reveals that the impact of the global financial crisis on potential growth has been short-lived. The analysis of the sources of potential growth reveals that weak total factor productivity growth performance and sizeable investment declines post-global financial crisis have been more than compensated by significant gains in potential employment. Potential employment growth has been the key driver of potential growth in recent years, reflecting growing working age population, and rising labor force participation, particularly among women, albeit starting from low levels.